Faktor Determinan Panjang Badan Bayi Lahir Pendek sebagai Faktor Risiko Stunting di Jawa Barat: Determinant Factors of Short Birth Length Baby as a Risk Factor of Stunting in West Java - Judiono Judiono; Witri Priawantiputri; Noormarina Indraswari; Mutiara Widawati; Mara Ipa; Ginna Megawati; Heni Prasetyowati; Dewi Marhaeni (Universitas Airlangga, 2023)
Background: Short birth length is one of the predictors of stunting. Objectives: This study aimed to examine birth length's determinants, which are risk factors for stunting in later life. Methods: Analytical observational study with a cross-sectional approach used secondary data from the Indonesia Nutrition Status Survey (SSGI) in 2021. The population was households representing 33 provinces. The study sample was the babies recorded in the 2021 SSGI study in the West Java census block, with as many as 7,112 babies. The data collected were the birth length of the baby, factors when the mother was pregnant with the baby such as the mother's age, place of residence, mother's education level, occupation, ownership of JKN/Jamkesda, ever received blood supplement tablets, place of delivery, birth attendant, possession of a prosperous family card, social welfare economy, and several family members. Data were analyzed by bivariate and multivariate. The eligible variables were analyzed by multiple logistic regression tests with a significance level of p<0.05. Results: The results of the multivariate analysis showed that the factors affecting the length of the child's body at birth were the ownership of health insurance (JKN) and the acceptance of blood supplement tablets (TTD). The study found that mothers who did not have health insurance (JKN) were at risk for giving birth to babies with a short body length of 4.526 times. Mothers who received blood supplement tablets were 0.196 times less likely to have a baby with short body length than mothers who had never received blood supplement tablets. Conclusions: Factors that affect short birth length are JKN/Jamkesmas ownership and acceptance of blood supplement tablets. It is recommended that specific nutrition interventions be continued through the provision of blood supplement tablets and sensitive nutrition interventions through health insurance programs in prevention.